PENERAPAN CUSTOMER RELATIONSHIP MANAGEMENT (CRM) UNTUK OPTIMALISASI KEPUASAN PELANGGAN DI PT BINTANG BAHAGIA KALINDO - Hasan, Golan; Febiana, Jessica; Angeline, Dewi; Tan, Angelica; Fernando, Figo; Justin, Justin (Bussman Journal : Indonesian Journal of Business and Management, 2025)
The implementation of Customer Relationship Management (CRM) is an important strategy in increasing customer satisfaction at PT Bintang Bahagia Kalindo. This research aims to analyze the effectiveness of CRM in building long-term relationships with customers and increasing their loyalty to the company’s products and services. The research method used is a qualitative approach with interviews and observations of the implemented CRM strategy. The results show that optimal CRM implementation, such as service personalization, customer database utilization, and responsive communication, has a positive impact on customer satisfaction. In addition, the integration of technology in CRM makes it easier for companies to understand customer needs and provide more effective services. Thus, CRM acts as a key factor in improving the competitiveness and business sustainability of PT Bintang Bahagia Kalindo.